If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(m + 3) + 24 = 69 Reorder the terms: 3(3 + m) + 24 = 69 (3 * 3 + m * 3) + 24 = 69 (9 + 3m) + 24 = 69 Reorder the terms: 9 + 24 + 3m = 69 Combine like terms: 9 + 24 = 33 33 + 3m = 69 Solving 33 + 3m = 69 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + 3m = 69 + -33 Combine like terms: 33 + -33 = 0 0 + 3m = 69 + -33 3m = 69 + -33 Combine like terms: 69 + -33 = 36 3m = 36 Divide each side by '3'. m = 12 Simplifying m = 12
| 2x+x+y=100 | | 7x(12/6-2)^2-6 | | h-27/-7=-9 | | 7x+55=3x+23 | | 9(m+1)=54 | | 3(s+22)+10=88 | | -12/r=-3 | | -c^2+c+30=0 | | -3(s+18)=-15 | | 6x+40=2x+4 | | 6(k-74)-5=83 | | 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 |